A Large-Bandwidth Electro-Optic Modulator with U-T Double-Layer Traveling-Wave Electrode Structure Based on Thin-Film Lithium Niobate - Yuxiang Hao; Haiou Li; Yue Li; Haisheng Li; Yingbo Liu; Jiayu Yang; Liangpeng Qin (Photonics)
Thin-film lithium niobate (TFLN) electro-optic modulators serve as critical components in microwave photonic systems. To improve device performance, we developed a U-T double-layer traveling-wave electrode configuration. Using finite element analysis, we systematically simulated and optimized both modulation efficiency and radiofrequency characteristics, ultimately realizing a low half-wave voltage-length product of 1.77 V·cm, a minimal optical loss of 0.022 dB/cm, and an ultra-wide modulation bandwidth surpassing 100 GHz.